The Expression of T Cell FOXP3 and T-Bet Is Upregulated in Severe but Not Euthyroid Hashimoto’s Thyroiditis - Stana Tokić; Mario Štefanić; Ljubica Glavaš-Obrovac; Sonja Jaman; Eva Novosadová; Jana Petrkova; Zdenka Navratilova; Mirjana Suver Stević; Martin Petrek (Mediators of Inflammation)
Hashimoto’s thyroiditis (HT) is an organ-specific autoimmune disorder characterized by progressive thyroid failure. Th1 and Treg subset of CD4+ cells have been implicated in the pathogenesis; however, less is known about their respective roles across the spectrum of HT clinical presentations. To shed more light on CD4+ subsets role in HT, we investigated the mRNA expression levels of several Th1/Treg-associated transcription factors (T-bet/ETS1, HIF1α/BLIMP1/FOXP3) in peripheral blood T cells of 10 hypothyroid, untreated HT patients, 10 hypothyroid patients undergoing hormone replacement therapy, 12 euthyroid HT subjects, and 11 healthy controls by the qRT-PCR. Compared to euthyroid HT patients and controls, both hypothyroid (2.34-fold difference versus controls, P<0.01) and thyroxine-supplemented patients (2.5-fold, P<0.001) showed an increased FOXP3 mRNA expression in T cells. Similarly, mRNA expression levels of T-bet were upregulated in severely affected but not in euthyroid HT subjects (2.37-fold and 3.2-fold, hypothyroid and thyroxine-supplemented HT patients versus controls, resp., P<0.01). By contrast, no differences in mRNA expression levels of ETS1, BLIMP1, and HIF1α were observed across the study groups. In summary, severe but not euthyroid HT was associated with robust upregulation of T-bet and FOXP3 mRNA in peripheral T cells, independent of the thyroid hormone status but proportional to disease activity.